School leadership in facilitating deep learning-oriented instruction: a case study within the indonesian independent curriculum - Erlina Cahyana; Agung Hartoyo; Imran (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The shift toward 21st-century learning emphasizes the development of critical thinking, creativity, collaboration, and communication skills. However, observations at SMA Negeri 1 Anjongan indicate that students’ literacy and conceptual understanding remain at a moderate level, as reflected in difficulties with analytical and reasoning tasks. This condition suggests the persistence of surface learning rather than deep learning, alongside limited optimization of school leadership in supporting the implementation of the Indonesian Independent Curriculum. Aims: This study aims to analyze the managerial leadership of the school principal, identify strategies employed to support deep learning-oriented instruction, and develop a conceptual model for transforming 21st-century learning practices. Method: A qualitative case study approach was employed involving one principal, one vice principal, five teachers, and three students selected through purposive sampling. Data were collected through interviews, observations, and document analysis, and analyzed using the Miles, Huberman, and Saldaña model. Data validity was ensured through source, technique, and time triangulation. Results: The findings reveal that deep learning implementation is strongly influenced by systematic leadership practices. Three key strategies were identified: integration of deep learning into instructional planning, application of active learning approaches such as discussion, project-based learning, and problem-solving, and continuous reflective academic supervision. These strategies contributed to increased student engagement and participation. Conclusion: The study proposes a three-stage leadership model consisting of strategic planning, innovative implementation, and continuous evaluation, serving as a framework for integrating the Independent Curriculum with deep learning-oriented instruction.